Implementasi Kurikulum Merdeka Di RA Ihsaniyah Kecamatan Sumberasih Probolinggo - Jannah, Rohimah; Eka Dheasari, Agustiarini (Prodi Pendidikan Guru Pendidikan Anak Usia Dini, 2025)
The Merdeka Curriculum emphasizes freedom in education and learner-centered learning, to create a dynamic learning environment. However, its implementation often does not fully achieve optimality in encouraging active learning. This study aims to examine the application of the Merdeka Curriculum in shaping active learning at RA Ihsaniyah, Semberasih District, Probolinggo. The method used is descriptive qualitative with research participants consisting of the principal, 2 teachers, and the deputy curriculum field. Data were obtained through direct observation and interviews, and then analyzed through the process of data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the Merdeka Curriculum involves three main stages, namely planning, implementation, and evaluation of active learning. However, several obstacles were found in the process, such as the need for adaptation to the new curriculum, limited facilities and infrastructure, and the level of teacher competence that still needs to be improved. This study recommends that RA Ihsaniyah better prepare adequate infrastructure and conduct training to improve teacher competence. This step is important to support the maximum implementation of the Merdeka Curriculum in creating an active and development-oriented learning environment for children.